Melatih Kreativitas Anak Sekolah Dasar dengan Menciptakan Karya Seni Lukis Berbahan Alam - Zuliani Fauziah; Bela Dwi Nur Cahyani; Lailatun Nikhlah; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to determine the influence of painting with natural materials on the development of elementary school children's creativity. Through literature studies, this research analyzes various relevant publications to identify the concept of creativity, the benefits of using natural materials in art learning, as well as the results of previous research related to this topic. The research results show that painting activities with natural materials have great potential in stimulating children's creativity through various aspects, such as critical thinking skills, imagination and self-expression. Apart from that, this activity can also improve fine motor skills, hand-eye coordination, and environmental awareness in children. The use of a variety of natural materials and their multisensory nature can provide a fun and meaningful learning experience for children, thereby encouraging their interest and motivation to learn.